Scholastic book of world records 2020 - O'Brien, Cynthia (Cynthia J.); Mitchell, Abigail; Bright, Michael; Sommerville, Donald, 1957- (New York, NY : Scholastic Inc., 2019)
A reference guide includes records in the realms of popular culture, sports, science, nature, and technology, and includes a section of United States records.
Music makers -- Screen and stage -- On the move -- Super structures -- High tech -- Amazing animals -- Incredible earth -- State stats -- Sports stars.
"Scholastic Summer Reading Challenge Results Inside!"--Cover
Includes index.
Keywords: Curiosities and wonders -- Juvenile literature; World records -- Juvenile literature; Curiosities and wonders; World records; Curiosities and wonders; World records; Illustrated works; Informational works; Juvenile works; Trivia and miscellanea; Trivia and miscellanea; Illustrated works; Informational works